Possíveis causas do declínio do órgão no Brasil - Kerr, Dorotéa Machado (1985)
The object of the present study is to present the state of the pipe-organ in Brazil, which is clearly to be in decline. As an instrument which is basically liturgical, and which in Brazil is directly connected with the Roman Catholic Apostolic Church, the pipe-organ has always been subject to all the modifications through which the Church, the liturgy and sacred music have passed. The starting point of this study was the observation that, after the Council of Vatican II, the situation of the pipe-organ in Brazil presented significant changes: a decrease in its utilization in the liturgy and an increase in the number of instruments not only abandoned, but actually destroyed. The plan of this research consists of a study of tendencies, based firstly on a historical description of the instrument since the beginning of colonial times in Brazil up to the present date; secondly on the study of the present situation based on information received by means of questionnaires sent to churches; interviews; and the Catalogue of Pipe-organs in Brazil, which constitutes volume II of this work. The basic hypothesis was that the liturgical changes since Vatican II constitute the preponderent factor for the present decline of the instrument in this country, a decline which is shown not only in the loss of its liturgical-musical function, but equally in the interruption of the building and installation of nationally produced pipe-organs. The development of the work showed this to be the predominate factor, aided by economic, social and cultural problems. The Catalogue of Organs of Brazil, although inicial, through the description of many instruments, also elucidates elements which help to comprehend the actual state of the pipe-organs in Brazil.